Lesotho: Agricultural R&D indicators factsheet update - Mohloboli, Maleoa; Beintema, Nienke M.; Flaherty, Kathleen (Department of Agricultural Research, 2018)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also features a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.